PS-B02-1: UPREGULATION OF KEY GENES ELN AND TGFB3 WERE ASSOCIATED WITH THE SEVERITY OF CARDIAC HYPERTROPHY. (January 2023) - Zhang, Rui; Xu, Xuan; Chen, Xi; Hao, Chunshu; Ji, Zhenjun; Zuo, Pengfei; Yang, Mingming; Ma, Genshan; Li, Yongjun
Abstract : Background: Hypertension induced cardiac hypertrophy is one of the most common pre-diseases of heart failure. This study aimed to identify the key pathogenic genes in the process of disease. Methods: GSE18224 was re-analyzed and obtained the differentially expressed genes (DEGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were carried out. Networks of transcription factor (TF)-mRNA, microRNA (miRNA)-mRNA and Protein-Protein interaction (PPI) were constructed, and key module was further screened out from PPI network. GSE36074 dataset and our constructed transverse aortic constriction (TAC) mouse model were both used for validating expression of genes in the module. Finally, the correlation between the genes and biomarkers of cardiac hypertrophy were evaluated. Results: Totally, there were 348 DEGs in GSE18224, which were mainly enriched in biological process including collagen fibril organization, cellular response to transforming growth factor beta stimulus and were involved in ECM-receptor interaction and Oxytocin signaling pathway, etc. There were 387 miRNAs targeted to 257 DEGs, while 177 TFs targeted to 71 DEGs. The PPI network contains 222 nodes and 770 edges, and 18 genes were screened out in the module. After validation, eight genes, which were also significantly upregulated in GSE36074, were selected out from the 18 DEGs. Two of the eight DEGs including Eln and Tgfb3 were also significantly upregulated in our mouse model of myocardial hypertrophy. Finally, the expression of Eln and Tgfb3 were both positively correlated with level of the disease biomarkers. Conclusion: Upregulated key genes Eln and Tgfb3 were positively correlated with the severity of cardiac hypertrophy, which will provide potential therapeutic targets for the disease.